STRATEGI PEMASARAN SYARIAH MELALUI MEDIA SOSIAL TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA E- COMMARCE SHOPEE - Putri, Febby Mutiara; Fasa, Muhammad Iqbal (STAI Darul Qalam Tangerang, 2024)
This research discusses the rapid development of the times and globalization causing society's needs to increase. Marketing effectiveness is very important so that consumers know and are interested in the products the business is marketing. Marketing aims to increase product awareness among consumers so that financing is more efficient and targeted. This research aims to find out how sharia marketing strategies through social media affect customer satisfaction and loyalty on Shopee e-commerce. The method used is to use the approach used in this research is descriptive qualitative, which describes data from the research results obtained in more depth. One of the advantages of social media in marketing is that it has a lot of potential for use in a business. The important role of sharia marketing strategies through social media on customer satisfaction and loyalty on Shopee e-commerce